Peran Satuan Binmas Dalam Mencegah Tindak Pidana Curanmor Melalui Metode Penyuluhan di Wilayah Hukum Polresta Cirebon - Agung, Agung Setyo Utomo (Indonesian Journal of Police Studies, 2020)
The background from this problem arises because of cases of vehicle theft by the community in Cirebon District. The research aims to knows that counseling as a method by the Police Binmas Unit in Cirebon District whether it is in accordance with its role in carrying its duties and the factors that influence the counseling method both those that support or hinder the duties of the Binmas Unit. Concepts and theories are used to analyze the focus of research. The research concept includes counseling methods used to prevent vehicle theft, Binmas Unit in delivering messages, concept of role, concept of vehicle theft, Police Chief Regulation Number 21 Year 2007, and Police Chief Regulation Number 3 Year 2015. Theories include Communication Theory and SWOT Analysis. Research method by systematic is qualitative approach. This type of research is descriptive analytic. Data sources from primary and secondary. Data collection techniques with interviews, observation, and document analysis. The location is at the Police Binmas Unit Cirebon District. Validity with data triangulation. Data analysis uses data reduction, data presentation, and drawing conclusions. The results found that the implementation of counseling that was analyzed by Police Chief Regulation Number 21 of 2007 and Communication Theory had not been fully implemented. The influencing factors are internal factors and external factors that are analyzed by SWOT analysis consisting of the vulnerability social conditions of the Cirebon District, supporting factors from other functions, response from the community, Relationship Procedure for Work and Binmas Unit personel. Conclusion of the implementation of counseling as a method by Binmas Unit to prevent the case of vehicle theft can be run even though it is not yet completely perfect so that the Binmas Unit has not fully carried out it’s role to prevent vehicle theft. Constructive suggestion includes suggestions for carrying out counseling to deliver a message of prevention of vehicle theft to the community to be better and take advantage of internal and external factors that support the task of Binmas Unit through counseling methods.